Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jnm.3048
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of MgZnO/ZnO heterostructure field effect transistor for power switching

Abstract: We investigate the power switching mechanism to evaluate the power loss (PD) and efficiency (ɳ) in MgZnO/ZnO (MZO)‐based power heterostructure field effect transistor (HFET), and physical parameters responsible for PD in molecular beam epitaxy (MBE) and dual ion beam sputtering (DIBS) grown MZO HEFT and compare the performance with the group III‐nitride HFETs. This work extensively probes all physical parameters such as two‐dimensional electron gas (2DEG) density, mobility, switching frequency, and device dime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…ZnO and its alloy heterostructure field effect transistors (HFETs) have been widely investigated as a very promising material for photodetectors, sensors, memory devices and high frequency switching applications due to the high * Author to whom any correspondence should be addressed. two-dimensional electron gas (2DEG) density along with the high conductance [1][2][3][4][5][6][7]. Khan and Kumar et al [8,9] have reported, the MgZnO/CdZnO (MCO) heterostructure is also promising structure for HFET application due to higher 2DEG (∼10 14 cm −2 ), high conductance (∼10 15 V −1 s −1 ), low sheet resistance (131 Ω), and high drain current density (∼400 mA mm −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…ZnO and its alloy heterostructure field effect transistors (HFETs) have been widely investigated as a very promising material for photodetectors, sensors, memory devices and high frequency switching applications due to the high * Author to whom any correspondence should be addressed. two-dimensional electron gas (2DEG) density along with the high conductance [1][2][3][4][5][6][7]. Khan and Kumar et al [8,9] have reported, the MgZnO/CdZnO (MCO) heterostructure is also promising structure for HFET application due to higher 2DEG (∼10 14 cm −2 ), high conductance (∼10 15 V −1 s −1 ), low sheet resistance (131 Ω), and high drain current density (∼400 mA mm −1 ).…”
Section: Introductionmentioning
confidence: 99%